2017
DOI: 10.1002/2016gb005407
|View full text |Cite
|
Sign up to set email alerts
|

Multiple metabolisms constrain the anaerobic nitrite budget in the Eastern Tropical South Pacific

Abstract: The Eastern Tropical South Pacific is one of the three major oxygen deficient zones (ODZs) in the global ocean and is responsible for approximately one third of marine water column nitrogen loss. It is the best studied of the ODZs and, like the others, features a broad nitrite maximum across the low oxygen layer. How the microbial processes that produce and consume nitrite in anoxic waters interact to sustain this feature is unknown. Here we used 15 N-tracer experiments to disentangle five of the biologically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
96
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 79 publications
(111 citation statements)
references
References 85 publications
(143 reference statements)
14
96
1
Order By: Relevance
“…OCN − , urea, and NH4+ uptake were also measured below the euphotic zone in the ODZ, and uptake rates of these compounds increased with depth and exceeded rates of anammox attributed to those same substrates at the SNM (Fig. ; Babbin et al ). Uptake rates of all three N compounds were of similar magnitude within the ODZ (0.1–0.5 nmol N L −1 h −1 ; Fig.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…OCN − , urea, and NH4+ uptake were also measured below the euphotic zone in the ODZ, and uptake rates of these compounds increased with depth and exceeded rates of anammox attributed to those same substrates at the SNM (Fig. ; Babbin et al ). Uptake rates of all three N compounds were of similar magnitude within the ODZ (0.1–0.5 nmol N L −1 h −1 ; Fig.…”
Section: Discussionmentioning
confidence: 94%
“…Error bars are ± 1 SD (concentration, 29 N 2 production, n = 3) and ± 1 average deviation (uptake, n = 2). 29 N 2 production rates and NO3, NO2, and oxygen profiles are reproduced from Babbin et al ().…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This reoxidation dynamic has been invoked in other zones where NO 2 − accumulation occurs, particularly in ODZs of the global ocean (Beman et al, ; Buchwald et al, ; Füssel et al, ; Martin & Casciotti, ; Peters et al, ). Indeed, reoxidation of nitrite under anoxic conditions, while still not well understood, may underpin a greater part of the natural nitrogen cycle than previously recognized (Babbin et al, ; Granger & Wankel, ; Sun et al, ). For example, recent studies have suggested that the larger than expected Δδ 15 N values may actually be representative of isotopic equilibration between nitrite and nitrate, occurring in connection with highly reversible enzymatic activity (Figure b).…”
Section: Discussionmentioning
confidence: 98%